2011
DOI: 10.1111/j.1468-3083.2011.04286.x
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule inhibitor of Mitf‐E‐box DNA binding and its depigmenting effect in melan‐a cells

Abstract: The results show that Compound #17 is the first small molecule inhibitor of Mitf-E-box DNA binding with depigmenting activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…4, asiaticoside inhibits melanogenesis by interfering with the DNA binding of MITF. Similarly, Um et al (25) reported that {1-[2-(4-chloro-phenoxy)-ethyl]-1H-benzoimidazol-2-ylsulfanyl}-acetic acid inhibits melanogenesis by interfering with direct MITF binding to E-box DNA. In addition, MITF DNA binding is inhibited by PIAS3, a protein inhibitor of activated signal transduction and activator of transcription 3 (26).…”
Section: Discussionmentioning
confidence: 99%
“…4, asiaticoside inhibits melanogenesis by interfering with the DNA binding of MITF. Similarly, Um et al (25) reported that {1-[2-(4-chloro-phenoxy)-ethyl]-1H-benzoimidazol-2-ylsulfanyl}-acetic acid inhibits melanogenesis by interfering with direct MITF binding to E-box DNA. In addition, MITF DNA binding is inhibited by PIAS3, a protein inhibitor of activated signal transduction and activator of transcription 3 (26).…”
Section: Discussionmentioning
confidence: 99%
“…Along with regulation of neural crest genes, the expression and function of the MITF melanocyte specification factor is important in melanomas. Inhibition of MITF in melanomas can lead to apoptosis and cell cycle arrest (Du et al., 2004; McGill et al., 2002), and targeting MITF activity with small molecule inhibitors has been pursued as a therapeutic approach (Faloon et al., 2010; Um et al., 2012; Yokoyama et al., 2011). The expression level of MITF is critical to its function in melanocyte development and melanomas.…”
Section: Developmental Factors Supporting Melanoma Initiationmentioning
confidence: 99%